Unified theory of firm: an empirical analysis - Duasa, Jarita; Mhd. Sarif, Suhaimi; Abdul Sabian, Nur Arfifah (Emerald Publishing Limited, 2020)
Four main strategies required for firms to be able to achieve their main objectives in organizations under the unified theory of the firm are technological advance, intellectual development, spirituality conducts and customer satisfaction concern. This study aims to explore the inclination of firms to adopt all these strategies in, factors that contribute to the adoption of all these strategies and significant relationship between these strategies of firms in the context of Malaysian firms.